Improving Fifth-Grade Students’ Learning Activities and Learning Outcomes in Pancasila Education through the Think-Pair-Share Type of Cooperative Learning Model at SDN 01 Ulak Karang - Nosi Ageni Putri; Gusnita Efrina (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Pancasila Education requires active student engagement to promote conceptual understanding, cooperation, responsibility, and academic achievement in a balanced manner. However, classroom action research simultaneously examining learning activities and outcomes through Think-Pair-Share (TPS) among fifth-grade students remains limited. This study aimed to improve students’ learning activities and outcomes in Pancasila Education through the TPS cooperative learning model. Classroom action research was conducted across two cycles involving 26 purposively selected Grade VA students at SDN 01 Ulak Karang. Data were collected through classroom observations, non-test assessments, and learning achievement tests and analyzed using descriptive percentage analysis. The findings showed that students’ discussion activity increased from 45.51% in Cycle I to 78.69% in Cycle II, cooperation increased from 42.31% to 82.70%, and responsibility increased from 53.85% to 74.73%. The mean learning outcome score also increased progressively from 63.2 at the pre-action stage to 67.2 in Cycle I and 89.2 in Cycle II. These findings demonstrate that TPS can foster a more participatory and collaborative Pancasila Education classroom while improving students’ academic achievement. The study highlights the value of structured peer interaction, careful teacher facilitation, and reflective instructional improvement in implementing TPS. Further research should examine the sustainability of these improvements across broader school contexts and longer implementation periods.